2010
DOI: 10.1002/jclp.20749
|View full text |Cite
|
Sign up to set email alerts
|

The role of weight stigmatization in cumulative risk for binge eating

Abstract: Previous research supports a positive association between weight stigmatization experiences and binge eating. However, the extent to which weight stigmatization accounts for binge eating in the context of other risk factors requires further investigation. Using a cumulative risk model, we examine previously studied risk factors (environmental stress, psychological functioning, negative coping, body dissatisfaction) as well as weight stigmatization as predictors of binge eating bariatric patients and undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…Supported by previous studies, our findings suggest the eating disorder group had the highest level of reported WB (Ackard et al, 2011;Almeida et al, 2011;Durso & Latner, 2008). It is interesting to note that those who did not report any disordered eating had higher levels of psychological distress than those reporting disordered eating.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Supported by previous studies, our findings suggest the eating disorder group had the highest level of reported WB (Ackard et al, 2011;Almeida et al, 2011;Durso & Latner, 2008). It is interesting to note that those who did not report any disordered eating had higher levels of psychological distress than those reporting disordered eating.…”
Section: Discussionsupporting
confidence: 85%
“…Another study found a higher prevalence of WB among minorities, particularly African Americans . Conversely, Almeida, Savoy, and Boxer (2011) found lower rates of WB and binge eating risk factors among African Americans compared to their Caucasian and Latino counterparts. When examining eating disorders in a diverse low-income sample of college students, another research group found lower rates of eating disorders in African Americans and Caucasians compared to Latinos (Gentile, Raghavan, Rajah, & Gates, 2007).…”
mentioning
confidence: 83%
“…Weight stigma is also related to more extreme reforms of dysregulated eating. For example, perceived weight-based discrimination and teasing are related to increased binge eating (Almeida, Savoy, & Boxer, 2011; Durso, Latner, & Hayashi, 2012; Haines, Neumark-Sztainer, Eisenberg, & Hannan, 2006). …”
Section: Weight Stigma Undermines Self-regulation and Executive Functmentioning
confidence: 99%
“…Emerging research suggests that weight-based discrimination may be associated with binge eating among obese adults enrolled in behavioral weight loss programs [30] and adults seeking weight loss surgery [31]. Recently, it has been shown that, among a sample of college students, weight stigmatization experiences independently contributed to the prediction of binge eating behaviors above other risk factors for binge eating, such as negative coping strategies, body dissatisfaction, and perceived stress [32]. Interestingly, the increased risk for binge eating found among undergraduates was not seen among a sample of adult bariatric surgery patients who faced weight-based discrimination.…”
Section: Introductionmentioning
confidence: 99%